Effect of Anchote (Coccinia abyssinica) and Potato Starch Addition on Colloidal Stability of Pineapple Juice - Abebaw Teshome Tiruneh; Abebaw Ayele Negatu; Neela Satheesh (International Journal of Food Science)
Starch is one of the most important value-added food ingredients used as a thickener in many foods and industrial applications. This research investigated the effect of different concentrations of starch (anchote and potato) addition on the colloidal stability of pineapple juice. The experiment was carried out on a two-factor factorial design arranged in CRD. The first factor (starch type with two levels (anchote and potato)) and the second factor (starch concentration with three levels (1%, 3%, and 5%)) were considered. The starch-added juice samples were preserved for 15 days at room temperature. The physicochemical properties, colloidal stability, microbial counts, and sensory analysis were conducted in a 7-day interval including the first day. The results revealed that different starch concentrations showed a significant effect (P≤0.05) on the cloud stability, most of the physicochemical properties and microbial count of pineapple juice as compared to the control. The turbidity and viscosity of the juice samples were increased significantly (P≤0.05) by the starch addition; in contrast, pulp sedimentation and microbial counts were decreased. As storage duration increased, turbidity, viscosity, TSS, pH, and vitamin C content of juice decreased, whereas sedimentation, TA, and microbial count increased. The results revealed that the total bacterial and fungal counts of pineapple juice samples were rising as storage durations increased. The maximum cloud retention was observed in juice added with 5% anchote starch. Finally, it is confirmed that starch (anchote and potato) addition positively affected the colloidal stability of pineapple juice and also possessed high potential to extend the shelf life.